Diversity, difference and belonging in childhood: Issues for foster care and identities - Ann Phoenix (Social Work & Society, 2017)
Since the 1970s, those who support and those who oppose 'transracial' fostering and adoption have often been deeply divided. In transracial placements, diversity, difference and belonging are at the heart of developments in foster care and adoption. Yet, relatively little is currently known about how these issues impact on family practices and experiences. This paper aims to contribute to understanding of these issues by considering background issues necessary to informing policies and practices in foster care. It draws on the retrospective narratives of adults who grew up in visibly ethnically different households. The adults reported in this paper indicated that they crafted their racialized identities partly as the result of disjunctions in how they considered that other people saw them in relation to other members of their families. Their racialized identities (and those of people in their social networks) had an impact on how they dealt with, and felt about, these disjunctions. As a result, they crafted new understandings of their positioning and identities in ways that foregrounded difference, diversity and complex, contingent belonging to their families. It is often taken for granted that children living with their birth parent(s) are likely to feel that they belong in their families. However, the narratives produced in the study discussed below indicate that racialisation, in intersection with children's other social characteristics, can decentre straightforward ideas of belonging to their families and society. Belonging was linked with how they made sense of their racialisation and understood their positioning in it and in their families. The findings indicate that foster/adoptive parents need to recognize that racialisation and racism are important to the experiences of children in 'transracial' families, but that the impact on children is related to the intersection of the social categories in which they are positioned including, but not only, racialisation and ethnicisation.